(untitled) (المجلة العراقية للعلوم الاقتصادية, 2018)
The difference between the experimental sciences and the humanities is in the complexity and the multiplicity of its details. Therefore it is more difficult to study the humanities than the experimental sciences, and to apply the scientific research methods as well. The study of Economics, as a humanity science, and its analysis is not able to offer typical answers in order to solve the economic problem, and it is not able to put a limit for the contrasts which exist between many variables. For that reason and as a result there were numerous theories and economic thoughts. Each one of them present different ideology adopt its own thought to solve the economic problem.